2020
DOI: 10.1002/ejoc.202000619
|View full text |Cite
|
Sign up to set email alerts
|

From Rare Reagents to Rare Products: Regiospecific Silver‐Catalyzed [3+2] Cycloaddition of Aryl‐, Alkyl‐ and Aminosulfonyl Diazomethanes with Arenediazonium Tosylates

Abstract: The scope of silver nitrate‐catalyzed cycloaddition of arenediazonium salts has been expanded to include aryl‐ and alkylsulfonyl diazomethanes as well as the recently introduced diazomethyl sulfonamides. The reliance on these two classes of diazo compounds led to a new synthetic approach to the rare 2‐aryltetrazol‐5‐yl sulfones as well as to the synthesis of hitherto not described 2‐aryltetrazol‐5‐yl sulfonamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…CH-diazomethane sulfonamides 1 and their use in heterocycle synthesis. [3][4] The identity of all products reported herein were confirmed by 1 H and 13 C NMR spectroscopy as well as high-resolution mass-spectrometry. Some structures were unequivocally confirmed by single-crystal X-ray crystallography (Figure 4).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…CH-diazomethane sulfonamides 1 and their use in heterocycle synthesis. [3][4] The identity of all products reported herein were confirmed by 1 H and 13 C NMR spectroscopy as well as high-resolution mass-spectrometry. Some structures were unequivocally confirmed by single-crystal X-ray crystallography (Figure 4).…”
Section: Resultsmentioning
confidence: 54%
“…[2] In 2020, we described for the first time CH-diazomethane sulfonamides 1 which we showed to be competent synthons for the preparation of pyrazoles 2 (via dipolar cycloaddition with alkynes or β-nitrostyrenes) [3] and tetrazoles 3 (via silvercatalyzed dipolar cycloaddition with arene diazonium salts) (Figure 1). [4] An attractive aspect of this approach is the access to sulfamoyl-substituted heterocycles. The significance of sulfonamides in medicinal chemistry and drug discovery is indisputable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2020 work by the Krasavin group, it was demonstrated that (hetero)aryl-, alkylsulfonyl, and aminosulfonyl diazomethanes 435 are also applicable for this reaction [ 220 ]. Thus, the rare 2-aryltetrazol-5-yl sulfones and previously not described in the literature 2-aryltetrazol-5-yl sulfonamides 436 were prepared in generally good yields.…”
Section: Azoles With Four Heteroatomsmentioning
confidence: 99%
“…10 Recently, we described a new type of diazo reagents, CHdiazomethane sulfonamides 9, which were generated from tertiary α-acetyl-α-diazomethane sulfonamides 10 upon treatment with excess alumina. 16 CH-diazomethane sulfonamides 9 have been successfully involved in cycloaddition reactions with electron-deficient alkynes and olefins (to give pyrazoles), 16 with arenediazonium tosylates (in silver-catalyzed format, to give tetrazoles), 17 and, intramolecularly, with N-propargyl groups (to give pyrazole-fused sultams). 18 Thus we reasoned that α-acetyl- α-diazomethane sulfonamides 10 could, similarly to 6 (vide supra), be involved in a three-component synthesis of 1,5disubstituted 1,2,3-triazoline-4-sulfonamides 11, quite likely also in a diastereoselective fashion due to the nature of the 1,3dipolar cycloaddition process.…”
mentioning
confidence: 99%